Dual mediating effects of social support and fertility stress on mindfulness and fertility quality of life in infertile men: A case-control study - Abulizi, Maierhaba; Xu, Hua; Abuduguli, Alapate; Zhao, Wanzhu; He, Lijuan; Zhang, Chen (Frontiers in Psychology, 2023)
Background: Infertility is one of the three major public health problems in the world, bringing immense physical and psychological damage to men and affecting the quality of men’s reproductive life. Thus, the purpose of this study was to analyze the status of social support, fertility stress, mindfulness, and fertility quality of life in infertile men, and to explore the dual mediating effects of social support and fertility stress on mindfulness and fertility quality. Methods: A case control group study was conducted, with 246 men in the case group and 149 in the control group. The Social Support Scale, Fertility Stress Scale, Mindfulness Scale and Fertility Quality of Life Scale were used to establish a structural equation model using Mplus 8.3 to explore social support and fertility stress. Pathway relationships were drawn between mindfulness and fertility quality of life in infertile men. Results: There were significant differences between infertile and healthy men in each dimension of the core module of fertility quality of life, in the total score of the treatment module, in the total score of social support, in subjective and objective support, and in the total score of fertility stress, social pressure, sexual pressure, marital relationship, and childless pressure (P < 0.05 in each case). Further, the fertility quality of life in infertile men was positively correlated with mindfulness and social support, and negatively correlated with fertility stress (P < 0.05); mindfulness could directly affect the core and treatment modules of reproductive life quality, and indirectly affect the core of reproductive life quality through social support (mediation effect accounted for 19.0%), while the treatment module (mediation effect accounted for 13.7%), and the core module indirectly affected reproductive life quality through fertility stress (mediation effect accounted for 16.8%). Conclusion: The fertility quality of life of infertile men is not optimistic. Mindfulness-related interventions and programs can improve their fertility quality of life.